Attitude towards e-opinion leadership on the way consumers perceive brand related characteristics with the potential influence of bloggers - Ergin, Neşe (İstanbul Bilgi Üniversitesi, 2019)
The aim of this study is to explore the relationship between e-opinion leadership attributes and brand-related characteristics as perceived by consumers and find out whether e-opinion leadership plays a role in this process or not. In order to explore this relationship, the study mainly focuses on blogs for being influential platforms curated by bloggers, or in other words e-opinion leaders. In order to explore these potential relationships, 521 Internet-users aged between 18-40 were reached as participants. The a ge r ange i s c hosen a s 1 8-40 since the range is marked for mainly compassing university students, young female professionals, single non-working women, and housewives, who are among users of blogging services as contributors and readers. Findings revealed attitude towards e-opinion leadership determined brand involvement, brand image, brand loyalty, and brand trust. Regression analysis showed the highest relationship between brand loyalty and attitude towards eopinion leader (ß=,847, t=20,234, p=,000), followed by brand image (ß= ,715, t=22,423, p=,000) and brand involvement (ß= ,664, t=19,187, p=,000). Additionally, attitude towards e-opinion leader (ß= ,653, t=14.211, p=,000) was significantly determined by brand trust. E-opinion leadership has a decisive role on brand loyalty, brand participation, brand trust, and brand image, and e-idea leadership tendencies should be given importance in marketing and business activities on the Internet.

Bu araştırmanın amacı, e-fikir liderliği tutumu ile müşteriler tarafından algılanan markayla ilişkili karakteristik özelliklerin arasındaki ilişkinin incelenmesi ve bu süreçte e-fikir liderliğinin rolünün ortaya koyulmasıdır. Bu ilişkiyi incelemek için, araştırma bloggerler ya da diğer ifadeyle e-fikir liderleri tarafından tasarlanan etkili platformlar olan bloglar üzerine odaklanmıştır. Yaşları 18-40 arasında değişen 521 internet kullanıcısı katılımcı sayısına ulaşıldı. Yaş aralığı 18-40 olarak belirlenmiş olup, bu sayı temel olarak blog hizmetleri kullanan üniversite öğrencileri, genç kadın profesyoneller, çalışmayan bekar kadınlar ve ev hanımları ve okuyucuları içermesi bakımından seçilmiştir. Araştırma sonuçlarına göre, e-fikir liderliği tutumu marka katılımını, marka imajını, marka sadakatini ve marka güvenini belirlemektedir. Regresyon analizi sonuçlarına göre, e-fikir liderine karşı tutum ile marka bağlılığı arasında en yüksek ilişki (ß =, 847, t = 20,234, p =, 000), bulunmuş olup, bunu marka imajı (ß =, 715, t = 22,423, p =, 000) ve marka katılımı (ß= ,664, t=19,187, p=,000) izlemektedir. Buna ilave olarak, e-fikir liderliği tutumu (ß =, 653, t = 14.211, p =, 000) marka güvenini istatistiksel olarak anlamlı bir şekilde belirlemektedir. E-fikir liderliği marka sadakati, marka katılımı, marka güveni ve marka imajı üzerinde belirleyici bir role sahiptir ve internet üzerinden pazarlama ve işletme faaliyetlerinde e-fikri liderlik eğilimlerine önem verilmelidir.